2007
DOI: 10.1044/1092-4388(2007/103)
|View full text |Cite
|
Sign up to set email alerts
|

Training Japanese Listeners to Perceive American English Vowels: Influence of Training Sets

Abstract: Training protocols for learning non-native vowels should present a full set of vowels and should not focus only on the more difficult vowels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
91
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(100 citation statements)
references
References 24 publications
6
91
1
2
Order By: Relevance
“…For Japanese-accented Consonant items, the word-final /v/ was replaced with /b/, and the vowel /u/ was suffixed (move pronounced as / " mu:bu/). Just like Dutch, Japanese lacks the English vowel /ae/ in its inventory; unlike Dutch, however, Japanese distinguishes only five vowel qualities (Homma, 1992;Ladefoged, 1993;Shibatani, 1990), and Japanese learners of English tend to perceive and produce English /ae/ as /a/ (Aoyama, Flege, Guion, Akahane-Yamada, & Yamada, 2003;Carruthers, 2006;Nishi & Kewley-Port, 2007). Likewise, Japanese does not have labiodental fricatives, and Japanese learners often produce /b/ instead of English /v/ (Avery & Ehrlich, 1992;Thompson, 2001).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For Japanese-accented Consonant items, the word-final /v/ was replaced with /b/, and the vowel /u/ was suffixed (move pronounced as / " mu:bu/). Just like Dutch, Japanese lacks the English vowel /ae/ in its inventory; unlike Dutch, however, Japanese distinguishes only five vowel qualities (Homma, 1992;Ladefoged, 1993;Shibatani, 1990), and Japanese learners of English tend to perceive and produce English /ae/ as /a/ (Aoyama, Flege, Guion, Akahane-Yamada, & Yamada, 2003;Carruthers, 2006;Nishi & Kewley-Port, 2007). Likewise, Japanese does not have labiodental fricatives, and Japanese learners often produce /b/ instead of English /v/ (Avery & Ehrlich, 1992;Thompson, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…On average, Japanese participants responded correctly 97.3% of the time (with no significant differences between conditions (F 1 [2,82] Again, we would like to argue that Japanese-accented primes facilitated word recognition for Japanese listeners because the accent in the primes conformed with the language background of the listeners, and Dutch-accented primes facilitated word recognition because the primes were perceptually confusable with the English standard pronunciation for Japanese listeners. As in Experiment 1, Dutch-accented Vowel items contained the vowel /e/ (/ " hepi/) which is difficult to distinguish from /ae/ for Japanese listeners (e.g., Nishi & Kewley-Port, 2007); in contrast to Experiment 1, however, Consonant items in Experiment 2 involved /t/ (/in " di:t/), a phoneme that is contrasted in Japanese with /d/, though not in final position. While Mann (1992, 1994) have shown that Japanese listeners can nevertheless distinguish final /d/ quite well from /t/, other studies have failed to show this ability (Morrison, 2002).…”
Section: Experiments 2bmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Japanese ESL speakers tend to categorize the English vowel /I/ as the Japanese /i/ or /ii/ most of the time, yet they may also categorize the vowel as the Japanese =e <=, =e < e <=, or =e < i= (Strange et al, 1998;Strange et al, 2001). Similarly, a study by Nishi and Kewley-Port (2007) showed that when asked to identify the English vowel /I/, Japanese ESL speakers reported the English vowel /e/ most of the time.…”
Section: Introductionmentioning
confidence: 99%
“…Rather, the five spectrally distinct long-short vowel pairs (including /ɯ/ and /ɯɯ/) are identified mainly on the basis of F1 and F2, together with phonemic duration (Nishi & Kewley-Port, 2007).…”
mentioning
confidence: 99%